Studies of bimetallic nanocatalysts and synthesis of tricyclic pyrone molecules for Alzheimer’s disease - Tong, Zongbo (Kansas State University, 2022)
In the industry, 80% of products were produced by catalysts, and most of the catalysts are tiny particles with sizes less than 25 nm. In the first project (discussed in Chapter 1 and Chapter 2), we selected two types of bimetallic nanocatalysts (Pd/Au and Cu/Au) for our studies. The goals are to use the nanocatalysts (Pd/Au and Cu/Au nanoclusters) to produce products with opposite stereochemistry. A pair of chiral substituted poly-vinyl-N-pyrrolidones (CSPVP) were designed and synthesized for the stabilization of nanocatalyst colloids (in water or dimethylformamide) to synthesize products with opposite stereochemistry using different oxidants such as tertiary-butyl hydrogen peroxide (TBHP) or hydrogen peroxide. We first studied the nanocatalyst colloid using achiral poly-vinyl-N-pyrrolidones (PVP) to explore new catalytic reactions. Phthalan, indene, norbornene and their derivatives were applied to these nanocatalysts using 30% hydrogen peroxide or TBHP as oxidant. Results suggest that Cu/Au tends to activate sp3 carbons, and these carbons are connected to benzene ring or oxygen, while Pd/Au exhibits catalytic potential to oxidize sp2 carbons. Chapter 1 focuses on the syntheses of chiral polymers and the corresponding colloidal nanocatalysts. In the following chapter, a series of substrates were treated with nanocatalyst colloids in different ingredients. Some of these substrates were treated with CSPVP supported colloid, and results remain to be carefully studied. In the second project (discussed in Chapter 3), two tricyclic pyrones were synthesized for the investigation of Alzheimer’s disease in a rat model. We also attempted to synthesize a novel tricyclic pyrone to avoid the formation of two stereoisomers by the insertion of an alkene.
Keywords: Alzheimer’s disease; Bimetallic nanocatalysts; Polymer; Oxidation